(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the development of ecotourism and its impact on the lives of local families. It highlights positive aspects such as increased economic activity, job creation, and the formation of ecological awareness among families. The paper also discusses Uzbekistan’s potential in the field of ecotourism and the prospects for its further development.